Características comuns, regionais e idiossincráticas na dinâmica da dívida pública dos estados brasileiros - Silva, Wescley Soares (2017)
The objective of this study was to investigate the dimension of common regional and idiosyncratic characteristics in the public debt dynamics, individually observing the movements of the Net Consolidated Debt / GDP, the Primary Result / GDP and the Net Consolidated Debt / Net Current Revenue in the Brazilian states in the period from 2002 to 2014. It was sought to answer whether these variables were explained with greater emphasis by "shocks" from influences at the national level (Macroeconomic Policies, for example), or by changes at the regional / local level (greater tax inspection, higher spending control, greater industrialization, etc.). To that end, it was used the Bayesian model of latent dynamic factors, which allowed the decomposition of DCL / GDP, Primary Result / GDP and DCL / RCL into national, regional and specific state components. The results showed that, on average, the national factor was responsible for explaining approximately 87% and 77% of the volatility, respectively of the DCL / PIB and DCL / CLL of the states in general. Regarding the Primary Result, the idiosyncratic factor showed greater strength, explaining on average approximately 46% of the volatility in the states in general. In addition, it was found that the strength of the national factor decreased mainly after 2008, notably in relation to DCL / GDP. These results highlight, to a certain extent, that the dynamics of debt is impacted mainly by the national factor, and can be explained by the macroeconomic policy and legislative control of the indebtedness exercised by the central government. On the other hand, in relation to the primary result, the greater strength of the local factor in its volatility demonstrates, possibly, a greater autonomy of the states.